Numerical investigations of water-hammer with column-separation induced by vaporous cavitation using a one-dimensional Finite-Volume approach. (November 2018) - Daude, F.; Tijsseling, A.S.; Galon, P.
Abstract: Water-hammer with column-separation induced by cavitation is investigated numerically. The vapor–water flow is modeled using the Homogeneous Equilibrium Model in conjunction with the 1984 NBS/NRC Steam Tables. The discretization is done with the quasi 1-D Finite-Volume approach recently developed by the authors for compressible flows in pipelines. The ability of the present approach to tackle cavitating flows is first assessed. Then, comparisons with experimental results of water-hammer with column-separation demonstrate consistency with the present computations. Based on the obtained numerical results, focus is given to the dynamics of the liquid column-separation and to the associated physics such as cavitation, vapor growth and collapse, generation of the secondary water-hammer peak and the interaction of the primary and secondary pressure waves. The influence of the initial flow velocity before valve closure on the duration and size of the cavity and on the magnitude of the secondary water-hammer is examined.